Oligomerization of coronin: Implication on actin filament length in Leishmania. Issue 12 (13th January 2016) - Srivastava, Rashmi; Prasadareddy Kajuluri, Lova; Pathak, Neelam; Gupta, Chhitar M.; Sahasrabuddhe, Amogh A.
Abstract : Coronin proteins bind with actin filaments and participate in regulation of actin‐dependent processes. These proteins contain a coiled‐coil domain at their C‐terminus, which is responsible for their dimeric or trimeric forms. However, the functional significance of these oligomeric configurations in organizing the actin cytoskeleton is obscure. Here, we report that the Leishmania coronin exists in a higher oligomeric form through its coiled‐coil domain, the truncation of which ablates the ability of Leishmania coronin to assist actin‐filament formation. F‐actin co‐sedimentation assay using purified proteins shows that the coiled‐coil domain does not interact with actin‐filaments and its absence does not abrogate actin–coronin interaction. Furthermore, it was shown that unlike other coronins, Leishmania coronin interacts with actin‐filaments through its unique region. These results provided important insights into the role of coronin oligomerization in modulating actin‐network. © 2015 Wiley Periodicals, Inc.